Morphological features of connective tissue in experimental model of periodontitis, and orthodontic treatment in rats - Самойленко, Андрій Валерійович; Дрок, Вікторія Олександрівна (Actual Dentistry, 2019)
Background. The high prevalence of major dental diseases dictates the need to find optimal means, methods of prevention and treatment taking into account pathogenetic mechanisms of development. Therefore, the study of the structure of dental and associated somatic diseases, the establishment of dominant pathogenetic factors in dental diseases in patients with general-somatic pathology, which determine the choice of adequate therapeutic and prophylactic action, is relevant. Objektiv. To investigate the morphological changes occurring in the tissues of rats on which the experimental model of periodontitis with the defeat of connective tissue of the periodontium was reproduced for the experimental study of the pathogenesis of periodontitis and the development of methods of prevention and medical treatment of the disease. Methods. The experiment was conducted on 90 White Rat lines of the Vistar line, 3 months old, which were divided into 3 groups. At the stage of pre-morphological studies, indirect signs of periodontal disease were evaluated: behavioral changes in relation to eating; study of changes in the weight of rats; study of psychomotor activity. Subsequently, the animals were examined and assessed the condition of the parodont tissues according to the following criteria: teeth movement; the presence of inflammation of the gingival margin; tooth erosion. Results. The experimental model of periodontitis of rats made it possible to state that the osteoporotic changes of the bone of the alveolar retroperitoneum of experimental animals at the level of the incisors were accompanied by fallopian destructive changes of the periodontal complex, edema of the gingival margin, hyperemia, sluggish exudation and movement of teeth I, II and III degrees of severity, uneven erasing teeth. In the morphological study, in the bone of the alveolar processes of rats, the destruction of bone tissue by the type of smooth and osteoclastic resorption, and also necrotic changes in the epithelial attachment cells, was observed somewhere. Conclusions. The method of modeling periodontitis using kuprenil, hydrocortisone, modeling of orthodontic treatment allowed to shorten the duration of the experiment to 21 days, and get a more aggressive form of periodontitis. Key words: experimental modeling, rats, periodontitis.